(untitled) (Studia Doctoralia Psychology and Educational Science, 2025)
This study explores the relationship between workplace loneliness and counterproductive work behaviors, with a focus on the role of work meaningfulness as a moderating factor. In an empirical investigation conducted with a sample of 141 employees from various industries, we examined how perceptions of loneliness influence negative workplace behaviors and how work meaningfulness may diminish this effect. The results indicate that work meaningfulness acts indeed as a moderator in the relationship between loneliness and CWB, and despite the assumption that it would attenuate this relationship, work meaningfulness was found to work as an intensifier. In other words, high levels of perceived meaningfulness may cause a stronger effect of work loneliness on counterproductive work behavior. This study expands and contributes to existing literature regarding the outcomes of meaningful work. Moreover, the research implies that strategies to reduce loneliness and improve work meaning should be carefully designed, as they may have unintended consequences if not balanced properly.